The farnesoid X receptor agonist EDP‐305 reduces interstitial renal fibrosis in a mouse model of unilateral ureteral obstruction. Issue 6 (18th March 2019) - Li, Shen; Ghoshal, Sarani; Sojoodi, Mozhdeh; Arora, Gunisha; Masia, Ricard; Erstad, Derek J.; Ferriera, Diego S.; Li, Yang; Wang, Guogiang; Lanuti, Michael; Caravan, Peter; Or, Yat Sun; et al.
ABSTRACT: Farnesoid X receptor (FXR) is a nuclear receptor that has emerged as a key regulator in the maintenance of hepatic steatosis, inflammation, and fibrosis. However, the role of FXR in renal fibrosis remains to be established. Here, we investigate the effects of the FXR agonist EDP‐305 in a mouse model of tubulointerstitial fibrosis via unilateral ureteral obstruction (UUO). Male C57Bl/6 mice received a UUO on their left kidney. On postoperative d 4, mice received daily treatment by oral gavage with either vehicle control (0.5% methylcellulose) or 10 or 30 mg/kg EDP‐305. All animals were euthanized on postoperative d 12. EDP‐305 dose‐dependently decreased macrophage infiltration as measured by the F4/80 staining area and proinflammatory cytokine gene expression. EDP‐305 also dose‐dependently reduced interstitial fibrosis as assessed by morphometric quantification of the collagen proportional area and kidney hydroxyproline levels. Finally, yes‐associated protein (YAP) activation, a major driver of fibrosis, increased after UUO injury and was diminished by EDP‐305 treatment. Consistently, EDP‐305 decreased TGF‐β1—induced YAP nuclear localization in human kidney 2 cells by increasing inhibitory YAP phosphorylation. YAP inhibition may be a novel antifibrotic mechanism of FXR agonism, and EDP‐305 could be used to treat renal fibrosis.—Li, S., Ghoshal, S., Sojoodi, M., Arora, G., Masia, R., Erstad, D. J., Ferriera, D. S., Li, Y., Wang, G., Lanuti, M., Caravan, P., Or, Y. S., Jiang, L.‐J., Tanabe, K. K., Fuchs, B. C. The farnesoid X receptor agonist EDP‐305 reduces interstitial renal fibrosis in a mouse model of unilateral ureteral obstruction. FASEB J. 33, 7103–7112 (2019). www.fasebj.org